Механизм возникновения шумовых максимумов в элементах с нелинейными вольт-амперными характеристиками - Golovko, A. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
It is shown that the previously established mechanism for converting the current spectrum of conductivity fluctuations Sg(f) into voltage fluctuations Su(f) in a sample with a nonlinear voltage-current characteristic Su(f) = Sg(f)rdU (where rd is the differential resistance of the sample, U is the voltage drop across it) is confirmed in resistors, Schottky barriers, p–n junctions, varistors, and vacuum diodes.